Problem Based Learning Berbantuan Media Video Untuk Meningkatkan Ketuntasan Hasil Belajar Kognitif Peserta Didik Pada Materi Sistem Pernafasan Manusia - Sigit Prastiyo; Maria Ulfah; Eko Retno Mulyaningrum; Sudarman Rianto (Departement of Mathematics Education, 2023)
Abstract Respiratory system material is one of the materials that is difficult for students to understand. This is evidenced by the assessment of individual assessments which show that most students are under the KKM, namely 76 with classical completeness of 43.75% in the low category. Based on observations and interviews, teachers still apply conventional learning and do not use learning media so that it tends to make students passive and students' thinking processes do not develop optimally which results in cognitive values ​​that are not optimal. Therefore, it is necessary to increase the completeness of cognitive values, one of which is Problem Based Learning assisted by video media. Therefore, the purpose of this research is to increase the completeness of students' cognitive values ​​through the Problem Based Learning model assisted by video media on the subject of the human respiratory system. The research was conducted in class VIII G of SMP Negeri 37 Semarang with the implementation of Cycles I, II and III. Each cycle consists of four stages, namely planning, action, observation, and reflection. The implementation of the action includes 3 cycles adapted to the steps of the Problem Based Learning model, namely 1) orienting students towards problems, 2) organizing students 3) guiding individuals and groups, 4) developing and presenting work, 5) analyzing and assessing processes solution to problem. The results showed that the completeness of the cognitive scores of students in Cycle I was 65.60%, while in Cycle II it was 81.25%, in Cycle III it was 96.88%. Based on the research that has been done, it can be interpreted that the application of the Problem Based Learning model assisted by video media on the material of the human respiratory system can improve the completeness of students' cognitive values.